Anammox bacterial abundance and diversity in different temperatures of purple paddy soils by 13C-DNA stable-isotope probing combined with high-throughput sequencing - Yu, Zijie; He, Xinhua; Li, Zhitong; Zhou, Shuang; Guo, Dalu; Pu, Hao; Luo, Hongyan (Frontiers in Microbiology, 2023)
Introduction Anaerobic ammonium oxidation (anammox) plays a vital role in the global nitrogen cycle by oxidizing ammonium to nitrogen under anaerobic environments. However, the existence, abundance, and diversity of anammox bacteria between different temperatures are less studied, particularly in purple paddy soils. Methods 13C-DNA stable-isotope probe combined with Illumina MiSeq high-throughput sequencing was employed to explore soil abundance and diversity of anammox bacteria. In doing so, 40–60 cm depth soils from typical purple paddy soils in Chongqing, southwest China, were cultured under 12CO2-labeled and 13CO2-labeled at 35°C, 25°C, 15°C, and 5°C for 56 days. Results and Discussion Anammox bacteria were not labeled at all by 13CO2 at 5°C. The highest abundance of anammox bacteria was found at 25°C (3.52 × 106~3.66 × 106 copies·g−1 dry soil), followed by 35°C and 15°C (2.01 × 106~2.37 × 106 copies·g−1 dry soil) and almost no increase at 5°C. The relative abundance of Candidatus Jettenia sp. was higher at 25°C and 15°C, while Candidatus Brocadia sp. was higher at 35°C and 5°C. Our results revealed differences in anammox bacteria at different temperatures in purple paddy soils, which could provide a better understanding of soil N cycling regulated by anammox bacteria.